Fish reproductive biology : implications for assessment and management - Jakobsen, Tore (Chichester, West Sussex, U.K. ; Hoboken, NJ : John Wiley & Sons, 2016)
"This fully up-to-date, expanded and revised new edition has been written and compiled by some of the world's leading experts on fish reproduction and fisheries science. Following an introductory chapter, the book is broadly divided into three sections. The first section, Biology, Population Dynamics and Recruitment, covers recruitment in marine fish populations, reproductive dynamics, recruitment variability and the effects of fishing on fish populations. The book's second section concentrates on information critical to successful assessment and management, and includes in-depth information on egg, larval and juvenile surveys, stock identification and assessment models, predictions of catch and biomass, and the contribution of individual reproductive potential to recruitment and fisheries management. The book's final section covers the incorporation of reproductive biology and recruitment considerations into management advice and strategies, and includes chapters dealing with current paradigms and forms of advice, new approaches to management, and the implementation of information on stock reproductive potential in fisheries management. This excellent new edition provides vital information for fish biologists, fisheries scientist and managers, and should be found on the shelves of all libraries in universities and research establishments where biological sciences and fisheries management are studied and taught"--
"This excellent new edition provides vital information for fish biologists, fisheries scientist and managers, and should be found on the shelves of all libraries in universities and research establishments where biological sciences and fisheries management are studied and taught"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Fish stock assessment; Fishes -- Reproduction; Recruitment (Population biology); Fishery management; TECHNOLOGY & ENGINEERING / Fisheries & Aquaculture; Fish stock assessment; Fishery management; Fishes -- Reproduction; Recruitment (Population biology); Electronic books